Financing costs and barriers to entry in Australia's electricity market. Issue 6 (25th March 2021) - Rai, Alan; Nelson, Tim
Abstract : Purpose: This paper aims to provide investors' views on financing costs and barriers to entry into the electricity generation sector, with a focus on investors' views on potential impacts on cost of capital from adopting nodal pricing and financial transmission rights (FTRs). The implications for policymakers and policy reforms are also discussed in detail. Design/methodology/approach: Survey-based data collection of investors and developers in electricity generation, consisting of multiple choice questions from a closed list of discrete choices, binary-choice questions, and questions with free-text/open-ended answers. Findings: Across survey respondents, weighted-average cost of capital (WACCs) were broadly unchanged over 2019, with increases for undiversified/non-integrated participants offset by decreases for horizontally integrated participants. Cost of equity has risen, whereas cost of debt has fallen. Nodal pricing-cum-FTRs were estimated to increase WACCs by 150–200 basis points p.a. (15–20%), reflecting concerns around the firmness of FTRs and ability to automatically access intraregional settlement residues. Research limitations/implications: These findings have energy policy implications, namely, the need to consider the interaction between economic theory and real-world financing models when designing and implementing fundamental energy sector reforms. Practical implications: The need to consider implementation and transitional issues (e.g. grandfathering of existing rights, focusing on reducing the largest barriers to entry) is associated with implementing nodal pricing. Originality/value: Unique set of survey questions and insights that have not previously been addressed in an Australian context; what-if analysis not previously done in an Australian context